Buckled Germanene Formation on Pt(111). (20th May 2014) - Li, Linfei; Lu, Shuang‐zan; Pan, Jinbo; Qin, Zhihui; Wang, Yu‐qi; Wang, Yeliang; Cao, Geng‐yu; Du, Shixuan; Gao, Hong‐Jun
<x xml:space="preserve">Abstract</x> Germanene, a 2D honeycomb lattice analogous to graphene, is fabricated on a Pt(111) surface. It exhibits a buckled configuration with a (3 × 3) superlattice coinciding with the substrate's (√19 × √19) superstructure. Covalent bonds exist throughout the germanene layer. The resulting high‐quality germanene enables researchers to explore the fundamentals of germanene and its potential applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>